1998
DOI: 10.1055/s-2008-1080123
|View full text |Cite
|
Sign up to set email alerts
|

Subtalar Joint Arthrography

Abstract: The purpose of this study was to determine the accuracy and the specificity of an optimum technique of posterior talocalcaneal/posterior subtalar (PST) joint arthrography and anesthetic injection in patients with hindfoot pain. Fifty-five PST joints were studied in 55 patients. The posteromedial approach was used in the first 24 patients, followed by an anterolateral approach in 31 patients. The ease of performance, success of confirming PST needle position, and adverse effects were noted. After contrast injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 1 publication
0
52
1
Order By: Relevance
“…In the posterolateral injection approach the posterior subtalar joint space is projected freely, allowing fast puncture and easy correction of the puncture direction during the forward movement of the needle. A previous study reported that the posteromedial approach to the subtalar joint was deemed more difficult compared to the other approaches [16]. Furthermore, 4 patients out of 24 (17%) injected from posteromedially had unwanted anesthesia of the toes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the posterolateral injection approach the posterior subtalar joint space is projected freely, allowing fast puncture and easy correction of the puncture direction during the forward movement of the needle. A previous study reported that the posteromedial approach to the subtalar joint was deemed more difficult compared to the other approaches [16]. Furthermore, 4 patients out of 24 (17%) injected from posteromedially had unwanted anesthesia of the toes.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the posterolateral approach, no major nerves or vessels are at risk of being incidentally punctured. Kraus et al [16] reported that the posterolateral injection approach is also more accurate than the anterolateral approach even when imaging guidance is not used. This pilot study of short and medium term outcomes shows that there was a significant reduction in the mean NRS scores at all follow-up time points, particularly at 20-30 min after injection, but that only approximately onethird of patients reported clinically relevant improvement at 1 month on the PGIC scale.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations